Overexpression of Mineralocorticoid Receptors Partially Prevents Chronic Stress-Induced Reductions in Hippocampal Memory and Structural Plasticity. - Sofia Kanatsou (PLoS ONE, 2015)
Exposure to chronic stress is a risk factor for cognitive decline and psychopathology in genetically predisposed individuals. Preliminary evidence in humans suggests that mineralocorticoid receptors (MRs) may confer resilience to these stress-related changes. We specifically tested this idea using a well-controlled mouse model for chronic stress in combination with transgenic MR overexpression in the forebrain. Exposure to unpredictable stressors for 21 days in adulthood reduced learning and memory formation in a low arousing hippocampus-dependent contextual learning task, but enhanced stressful contextual fear learning. We found support for a moderating effect of MR background on chronic stress only for contextual memory formation under low arousing conditions. In an attempt to understand potentially contributing factors, we studied structural plasticity. Chronic stress altered dendritic morphology in the hippocampal CA3 area and reduced the total number of doublecortin-positive immature neurons in the infrapyramidal blade of the dentate gyrus. The latter reduction was absent in MR overexpressing mice. We therefore provide partial support for the idea that overexpression of MRs may confer resilience to the effects of chronic stress on hippocampus-dependent function and structural plasticity.